Under what institutional conditions does overseas business knowledge contribute to firm performance?. Issue 3 (June 2019) - Liu, Xiaohui; Xia, Tianjiao; Jiangyong, Lu; Lin, Daomi
Abstract: We examine the extent to which the impact of the overseas business knowledge transferred by returnee entrepreneurs on firm performance is conditional on institutional factors. The findings show that informal institutional differences between the home and host countries strengthen the positive impact of overseas business knowledge on the performance of returnee-founded firms. There is a complementarity between informal institutional differences and local government policy support which jointly enhance the positive impact of overseas business knowledge. However, a well-developed local business infrastructure substitutes for the impact of informal institutional differences on the relationship between overseas business knowledge and returnee venture performance.